Analisis Efektivitas Realisasi Anggaran Dana Desa Dalam Pembangunan (Studi Kasus Desa Jati Kec.Saguling Kab. Bandung Barat) - Nur Alam, Achmad Izwar; Kusmayadi, Dicki (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
In order to improve community welfare, the regional budget—which subsequently evolved into the Village Fund Budget in Jati Village was effectively used to realize village development. The study's focus, Jati Village in Saguling District, West Bandung Regency, West Java Province, used a Combination Method (Mix Methods) that included quantitative and qualitative techniques. Based on the study's findings, researchers came to the conclusion that the village fund budget was 99.10% effective in development, and that the realization rate was a respectable 99.37%. When a program or activity is carried out efficiently and in line with the goals established by the effectiveness of the village money allocation, positive outcomes are obtained. The community is encouraged to actively participate in development-related decision-making via the discussion process. While there are certain cases of village development that may lead to social and economic inequality between village communities that benefit from development and those that do not, the beneficial influence of development is mainly concentrated on community empowerment